Building performace and evaluation guide / Chris Gorse, Kambiz Rakhshanbabanari. - Gorse, Christopher A.; Rakhshanbabanari , Kambiz (Chartered Institute of Building, 2023)
This guide emphasises that taking a holistic approach can test building design and building performance pre-, during- and post-occupation. Our guide covers the various tests and methods used in evaluation, which inform clients, end-users, and practitioners of possible interventions that could close any performance gaps. This supports data collection and analysis in order that energy use can be understood and assessed against the energy performance expected.